Entry, multinational firms and exchange rate volatility - Katheryn Russ; Thomas A. Lubik (University of California, Department of Economics, 2006)
Recent discussions of exchange rate determination have emphasized the possible role of foreign direct investment in influencing exchange rate behavior. Yet, there are few existing models of multinational enterprises (MNEs) and endogenous exchange rates. This paper demonstrates that the entry decisions of MNEs can influence the volatility of the real exchange rate in countries were there are significant costs involved in maintaining production facilities, even when prices are perfectly flexible. For empirically plausible parameters, MNE activity can make the exchange rate much more volatile than relative consumption.
Keywords: C32; C47; C53; 330